Attitudes towards vegetables and fruits rich in bioactive compounds in a group of individuals aged 20-39 years old - Aleksandra Kureń; Magdalena Zegan; Ewa Michota-Katulska (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. Due to the high percentage of deaths caused by non-communicable chronic diseases, such as cancer or cardiovascular diseases, recorded in recent years, proper nutrition, including consumption of vegetables and fruit rich in bioactive compounds is of a vital importance. It is especially important in the light of consumers' interest in pro-health values of foods. Objective. Aim of this study, was to assess the attitudes of people aged 20-39 towards food with a specific health effect, with particular emphasis on selected vegetables and fruits rich in bioactive compounds. Material and methods. The study included 500 people aged 20-39 years old. The research tool was a questionnaire consisting of 3 parts, which assessed: attitudes of people aged 20-39 towards the health values of food, frequency of consumption of selected vegetables and fruits rich in bioactive compounds and knowledge about them. Results. The average result of respondents' given answers indicated their positive attitude towards health values of food (mean = 4.41). Nevertheless, consumption frequency of selected vegetables and fruits was low or very low among more than half (57%) of the respondents. In addition, members of the study group demonstrated insufficient knowledge about the confirmed by clinical tests, positive impact of the consumption of examined products on health (average knowledge test result = 25% among the members of the test group). At the same time, higher consumption of analysed vegetables and fruits was associated with better knowledge about them. Similarly, more positive attitudes towards health values of food were associated with higher frequency of vegetables and fruit consumption and knowledge about them. Conclusions. The surveyed adults aged 20-39 showed a positive attitude towards health values of food. Nevertheless, consumption of selected vegetables and fruits rich in bioactive compounds and knowledge about them was not sufficient. Due to the association between better knowledge about health values of particular products and frequency of their consumption, in the future, focus should be placed on increasing consumers' knowledge in this area, e.g. by organizing social and information campaigns.